2011
DOI: 10.1016/j.dci.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular responses of Ostrea edulis haemocytes to an in vitro infection with Bonamia ostreae

Abstract: Bonamiosis due to the parasite Bonamia ostreae is a disease affecting the flat oyster Ostrea edulis. B. ostreae is a protozoan, affiliated to the order of haplosporidia and to the cercozoan phylum. This parasite is mainly intracellular, infecting haemocytes, cells notably involved in oyster defence mechanisms. Suppression subtractive hybridisation (SSH) was carried out in order to identify oyster genes differentially expressed during an infection of haemocytes with B. ostreae. Forward and reverse banks allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 48 publications
(54 reference statements)
1
49
0
Order By: Relevance
“…S6C). Interestingly, the recent finding that FLN RNA is overexpressed in the hemocyte population of oysters infested with parasites (Morga et al, 2011) suggests that the FLN-positive hemocytes might indeed be lamellocytes.…”
Section: Research Articlementioning
confidence: 99%
“…S6C). Interestingly, the recent finding that FLN RNA is overexpressed in the hemocyte population of oysters infested with parasites (Morga et al, 2011) suggests that the FLN-positive hemocytes might indeed be lamellocytes.…”
Section: Research Articlementioning
confidence: 99%
“…The universal distribution of ChPTGER4 may indicate that is has a broader, more generalized role in numerous physiological processes in oyster. Previously, it was shown that hemocytes are the main immune tissue in invertebrates, especially in lower mollusks, and play a key role in the recognition of and defense against bacterial invasion and exogenous agents [36]. Thus, the high expression level of ChPTGER4 in hemocytes may suggest its potential function in the immune system of the Hong Kong oyster.…”
Section: Discussionmentioning
confidence: 99%
“…A gene encoding a galectin (Oe-Gal) has been completely characterized using suppression subtractive hybridization, carried out between infected and uninfected haemocytes. This gene appeared to be over-expressed in haemocytes within 1 h of contact with the parasites, suggesting that the Oe-Gal is involved in the recognition of the parasite (Morga et al 2011). Moreover, the cytoskeleton of the host cell seems to be involved in the internalization of the para site as suggested by the over-expression of a gene coding a filamin in infected haemocytes (Morga et al 2011) and the abundance of some genes related to the cytoskeleton in the libraries obtained from infected flat oysters (Martín-Gómez et al 2012).…”
Section: Host−parasite Interactionsmentioning
confidence: 99%
“…Recently, mechanisms of interaction between Bonamia spp. and their hosts, including mechanisms involved in the resistance to the disease, have been investigated in more depth at cellular and molecular levels (Morga et al 2009(Morga et al , 2011. Furthermore, it seems that in some cases, after their introduction, the parasites are only present at a low prevalence and with presumably limited effects on the population .…”
Section: Introductionmentioning
confidence: 99%